Effects of a high-fat diet on superoxide anion generation and membrane fluidity in liver mitochondria in rats - M Togo; N Konari; M Tsukamoto; R Kimoto; T Yamaguchi; H Takeda; I Kambayashi (Taylor & Francis Group, 2018)
Background Obesity is a primary factor of lifestyle-related diseases, and the age of its onset has decreased. The reactive oxygen species (ROS), the superoxide anion, is generated in the mitochondrial electron transport chain and the damage it induces in cells may be a contributing factor to obesity-related lifestyle diseases. In the present study, the influence of the ingestion of a high-fat diet (HFD) on superoxide anion generation in rat liver mitochondria (Mt) and membrane fluidity was investigated. Methods Male Wistar rats were fed a normal diet (ND, n = 6) or HFD (n = 6). Liver Mt were isolated and oxygen consumption, superoxide anion production (the adrenaline method), and membrane fluidity (the spin label method) were measured. Results After 11 weeks, body weights and abdominal circumferences were higher in the HFD group than in the ND group. Mt oxygen consumption was higher in the HFD group than in the ND group. Superoxide anion production was significantly lower in the HFD group than in the ND group, while no significant changes were observed in membrane fluidity. Conclusion Although rats developed diet-induced obesity, it did not reach the level of disease development. The promotion of lipid metabolism appeared to reduce superoxide anion production, but did not influence membrane fluidity. While superoxide anion damages cells as an oxidative stress, ROS and superoxide dismutase are essential signaling molecules in the body. The present results suggest that the continuous ingestion of a HFD impairs Mt and induces disease development.